Insecticide paints: a new community strategy for controlling dengue and zika mosquito vectors in Cabo Verde - Gómez, Lara Ferrero; Rocha, Hélio D. Ribeiro; Torró, Ignacio Gil; Pérez, Irene Serafín; Mendes, Deinilson Conselheiro; Silva, Keily L. Fonseca; Monteiro, Davidson D. Sousa Rocha; Dos Reis, Jailson P. Tavares; Leal, Silvânia Veiga; Soulé, Luis F. Vitória; Fortes, Jailton C.; Mendonça, Maria da Luz Lima; et al. (Frontiers in Tropical Diseases, 2024)
Background: Cabo Verde, an island country in West Africa, has been affected since human colonization by epidemics of vector-borne diseases with major epidemics of dengue and zika in recent years. Although there is a national program for integrated vector control, innovative strategies that reinforce routine activities and strengthen vector control are necessary to prevent the emergence or reemergence of arboviruses and new epidemics of dengue and zika. Insecticide paints are evidenced as new technologies for the formulation of insecticides in a more residual and safe way. TINTAEDES project aimed to assess the efficacy, acceptability, and operational deployment of an insecticide paint for Aedes control. Methodology/Principal findings: Laboratory and small-scale field trials were conducted, assessing mortality through World Health Organization cone bioassays. A community-based intervention study in the neighborhoods of Várzea and Tira Chapéu in the city of Praia, Cabo Verde, was developed. The intervention is a paint self-application model by homeowners and neighborhood volunteers. The intervention was evaluated based on entomological indicators and the responses given by the residents of the painted houses to a questionnaire on knowledge, satisfaction, and safety of insecticidal paints. A transfluthrin-based insecticide paint was effective against wild Ae. aegypti for one year in the laboratory and semi-field conditions. Residents largely perceived a reduction in mosquito presence in the treated houses (98%). Conclusion: Insecticide paints are presented as an effective innovation strategy for mosquito control, which could be implemented as a reinforcement of the measures carried out by the vector control program in the city of Praia and throughout the country.